A dual magnetic phase iron-based amorphous composite magnetic powder core, a preparation method and application thereof

CN122930716APending Publication Date: 2026-10-16GUANGDONG INST OF NEW MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611151551.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]针对现有磁粉芯绝缘包覆技术中存在的磁稀释效应显著、包覆剂耐热性差、高频损耗高、包覆均匀性难以控制以及电阻率与磁导率难以协同优化等不足,本发明提供了一种双磁性相铁基非晶复合磁粉芯的制备方法,通过采用具有本征磁性的自制油相Mn0.5Zn0.5Fe2O4作为包覆剂,替代传统的非磁性绝缘材料,在保证颗粒间电绝缘的同时,不降低磁导率,解决现有技术因包覆层非磁性而导致的磁性能下降问题;利用磁性包覆层与磁性粉末之间的磁耦合作用,减少传统非磁性层带来的磁通不连续性和畴壁钉扎效应,从而降低磁滞损耗和高频涡流附加损耗,提升磁粉芯在高频工况下的综合软磁性能

Benefits of technology

本发明采用具有本征磁性的Mn0.5Zn0.5Fe2O4作为包覆剂,替代传统的非磁性绝缘材料,形成具有磁性的包覆层,在颗粒间形成绝缘结构,且不产生非磁性“磁稀释”效应,甚至可通过磁耦合作用维持或提高磁粉芯的有效磁导率,解决了现有技术中为获得绝缘效果而牺牲磁性能的根本矛盾。同时,Mn0.5Zn0.5Fe2O4属于铁氧体材料,其电阻率远高于金属磁性粉末;作为包覆层能够有效切断磁性颗粒间的电接触,大幅提高磁粉芯的整体电阻率,从而显著降低高频涡流损耗,改善高频下的软磁性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930716A_ABST
    Figure CN122930716A_ABST
Patent Text Reader

Abstract

The application relates to a double-magnetic-phase iron-based amorphous composite magnetic powder core and a preparation method and application thereof, and belongs to the technical field of materials. 0.5 Zn 0.5 Fe2O4 as a coating agent, forms a magnetic coating layer, forms an insulating structure between particles, and does not produce a non-magnetic "magnetic dilution" effect. Meanwhile, Mn 0.5 Zn 0.5 Fe2O4 belongs to a ferrite material, and the resistivity is much higher than that of a metal magnetic powder; as a coating layer, the electrical contact between magnetic particles can be effectively cut off, the overall resistivity of the magnetic powder core is greatly improved, high-frequency eddy current loss is significantly reduced, and the soft magnetic performance under high frequency is improved. The iron-based amorphous composite magnetic powder core provided by the application has a loss as low as 242.28kW / m 3 , and the magnetic permeability is between 60 and 75, and is suitable for high-frequency power electronic devices such as new energy vehicles, DC / DC converters, data center power modules, photovoltaic inverters and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, and in particular to a dual-magnetic-phase iron-based amorphous composite magnetic powder core, its preparation method, and its application. Background Technology

[0002] Magnetic powder cores are a type of soft magnetic composite material, typically produced by coating magnetic alloy powder with an insulating material, mixing it with a binder, and then pressing it into shape. This material utilizes the insulating structure formed between the magnetic alloy powders to effectively improve resistivity and reduce eddy current losses, thus meeting the application requirements of magnetic components in power electronics fields such as new energy vehicles, data centers, and photovoltaic energy storage. With the rapid development of electronic components towards higher frequencies and miniaturization, various emerging industries are placing higher performance demands on magnetic powder cores. Developing high-performance metal magnetic powder cores that combine low loss and excellent frequency stability has become a current research focus.

[0003] Limited by the ability to form amorphous materials, the preparation of nanocrystalline magnetic powder cores usually adopts the following process: First, the amorphous ribbon is mechanically crushed to obtain amorphous flake powder, then the powder is organically or inorganically insulatingly coated, then the coated magnetic powder is pressed into magnetic powder cores of a specific size, and finally, after appropriate stress-relief crystallization heat treatment, nanocrystals are precipitated on the amorphous matrix to form an "amorphous + nanocrystalline" two-phase structure, thereby obtaining a high-performance nanocrystalline magnetic powder core. It is worth noting that the coating process of the powder is the key link that determines the comprehensive performance of the magnetic powder core, and its insulating coating effect directly affects the electromagnetic performance of the magnetic powder core. Therefore, the insulating coating process is regarded as one of the most core technologies in the preparation of magnetic powder cores, and it is also an important research direction in this field in recent years. Although the existing insulating coating process has improved the resistivity of the magnetic powder core and reduced the eddy current loss to a certain extent, it still has the following shortcomings: (1) The insulating coating agents currently widely used are mostly organic resins or inorganic non-magnetic materials. These materials themselves are not magnetic. After coating, they will form a non-magnetic isolation layer between magnetic powder particles. Although the resistivity is increased, the effective permeability of the magnetic powder core is inevitably reduced, resulting in a magnetic dilution effect. (2) The key stress relief heat treatment temperature in the preparation of nanocrystalline magnetic powder cores is usually high (400-700℃) to promote the precipitation of nanocrystals in the amorphous matrix. However, organic coating agents are prone to decomposition, carbonization or softening failure at this stress relief heat treatment temperature, resulting in the destruction of the insulation structure and a sharp increase in eddy current loss. Even if inorganic coating agents with relatively good heat resistance are used, microcracks are often generated due to the mismatch between the thermal expansion coefficient of the magnetic powder matrix, which reduces the integrity and long-term reliability of the coating layer. (3) The non-magnetic insulation layer will hinder the movement of magnetic domain walls and the rotation of magnetic moments, resulting in an increase in hysteresis loss. At the same time, under the action of AC magnetic field, the magnetic flux discontinuity between the non-magnetic layer and the magnetic layer will induce local eddy currents and additional losses, which will degrade the loss characteristics of the magnetic powder core at high frequency and make it difficult to meet the increasingly stringent requirements of high frequency and low loss applications. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a dual-magnetic-phase iron-based amorphous composite magnetic powder core, its preparation method, and its application.

[0005] To address the shortcomings of existing magnetic powder core insulation coating technologies, such as significant magnetic dilution effect, poor heat resistance of coating agents, high high-frequency loss, difficulty in controlling coating uniformity, and difficulty in synergistically optimizing resistivity and permeability, this invention provides a method for preparing a dual-magnetic-phase iron-based amorphous composite magnetic powder core. This method utilizes a self-made oil phase Mn with intrinsic magnetic properties. 0.5 Zn 0.5Fe2O4, as a coating agent, replaces traditional non-magnetic insulating materials. While ensuring electrical insulation between particles, it does not reduce magnetic permeability, solving the problem of decreased magnetic performance caused by the non-magnetic coating layer in existing technologies. By utilizing the magnetic coupling effect between the magnetic coating layer and the magnetic powder, it reduces the magnetic flux discontinuity and domain wall pinning effect caused by traditional non-magnetic layers, thereby reducing hysteresis loss and high-frequency eddy current additional loss, and improving the overall soft magnetic performance of the magnetic powder core under high-frequency operating conditions.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing a dual-magnetic-phase iron-based amorphous composite magnetic powder core, comprising the following steps: S1. Mix amorphous FeSiB magnetic powder with phosphoric acid, coat the surface of the amorphous FeSiB magnetic powder with a phosphoric acid passivation layer, and then add Mn. 0.5 Zn 0.5 Fe2O4 organic solvent dispersion was thoroughly mixed to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder is 1~4:200; the Mn 0.5 Zn 0.5 The average particle size of Fe2O4 is 15~50nm; S2. The coated magnetic powder from step S1 undergoes a first annealing process to remove stress and solidify the coating layer, resulting in annealed coated magnetic powder. This first annealing is a dual treatment of "stress relief + coating layer solidification" for the magnetic powder. Phosphoric acid reacts with the magnetic powder surface to form a phosphate passivation layer. Heating and annealing further densify and stabilize this passivation layer, and also allow Mn to... 0.5 Zn 0.5 Fe2O4 particles are firmly anchored on the surface of FeSiB magnetic powder; S3. Mix the silicone resin with the annealed coated magnetic powder from step S2 until fully mixed; then add the lubricant and mix thoroughly to obtain iron-based amorphous composite magnetic powder. S4. The iron-based amorphous composite magnetic powder from step S3 is cold-pressed to form a blank; S5. The blank from step S4 is subjected to a second annealing to remove the internal stress generated during the cold pressing process, thereby obtaining an iron-based amorphous composite magnetic powder core.

[0007] This invention utilizes Mn with specific addition amounts and specific particle sizes. 0.5 Zn 0.5 Fe2O4 is used as a coating agent to coat the surface of magnetic powder, Mn 0.5 Zn 0.5 Fe2O4 particles have a particle size of 15nm~50nm, which can effectively coat the surface of amorphous FeSiB powder (100μm). Mn 0.5Zn 0.5 Fe2O4, as a Mn-Zn ferrite, possesses both a high Ms value and a high bulk resistivity (10). 2 ~10 8 Ω), which can effectively alleviate the magnetic dilution effect. Mn 0.5 Zn 0.5 Fe2O4 was used as a coating agent to prepare iron-based amorphous composite magnetic powder cores, and Mn 0.5 Zn 0.5 Fe2O4 is used simultaneously as both an insulating coating layer and a magnetic phase to construct a "dual magnetic phase structure." The magnetic insulating coating layer is used to synergistically improve the resistivity and permeability of the composite magnetic powder.

[0008] The dual-magnetic-phase iron-based amorphous composite magnetic powder core of the present invention must be subjected to a two-stage annealing process. The FeSiB magnetic powder with phosphate passivation and ferrite coating needs to be annealed first. After annealing, binders such as resin and lubricants such as zinc stearate are added and coated again. A second annealing is required. The two annealing steps cannot be omitted. Missing either annealing step will lead to a decrease in the magnetic properties of the composite magnetic powder core.

[0009] In a preferred embodiment of the preparation method described in this invention, in step S1, Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder is 2~4:200 (more preferably 2:200). The composite magnetic powder core prepared at this ratio has better magnetic properties.

[0010] In a preferred embodiment of the preparation method described in this invention, in step S1, the mass ratio of phosphoric acid to amorphous FeSiB magnetic powder is 1~2:200.

[0011] In a preferred embodiment of the preparation method described in this invention, in step S1, the mass ratio of phosphoric acid to amorphous FeSiB magnetic powder is 1:200. The composite magnetic powder core prepared at this ratio exhibits superior magnetic properties.

[0012] In a preferred embodiment of the preparation method described in this invention, in step S1, the Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is as follows: Ferric chloride hexahydrate, sodium oleate, n-hexane, anhydrous ethanol, and deionized water are mixed and stirred, then degassed at 60℃. The organic phase is separated, and n-hexane is evaporated to obtain an iron-oleic acid complex. The obtained iron-oleic acid complex is then mixed with oleic acid, 1-octadecene, and diphenyl ether. Under nitrogen protection, the mixture is heated to 200℃, then increased to 300℃ at a rate of 10℃ / min and held for 30 min. After the reaction, the mixture is washed with ethanol, collected by centrifugation, dispersed in n-hexane, and the solvent is evaporated to obtain magnetic nanoparticles Mn. 0.5 Zn 0.5 Fe2O4.

[0013] In a preferred embodiment of the preparation method of the present invention, in step S1, the organic solvent includes n-hexane, acetone or ethanol.

[0014] As a preferred embodiment of the preparation method of the present invention, in step S2, the first annealing condition is to hold at 300~400℃ for 30~90min.

[0015] In a preferred embodiment of the preparation method described in this invention, in step S2, the first annealing condition is to hold at 350°C for 60 minutes.

[0016] In a preferred embodiment of the preparation method of the present invention, in step S3, the mass ratio of the organosilicon resin to the annealed coated magnetic powder is 1:100~200. In a preferred embodiment of the preparation method of the present invention, in step S3, the mass ratio of the lubricant to the annealed coated magnetic powder is 1:100~1000; In a preferred embodiment of the preparation method of the present invention, in step S3, the organosilicon resin includes methyl silicone resin or phenylmethyl silicone resin; the lubricant includes zinc stearate or magnesium stearate.

[0017] In a preferred embodiment of the preparation method of the present invention, in step S4, the pressure of cold pressing is 1000~3000 MPa.

[0018] In a preferred embodiment of the preparation method described in this invention, in step S5, the conditions for the second annealing are 400~600℃ for 10~180 min.

[0019] In a preferred embodiment of the preparation method described in this invention, in step S5, the second annealing condition is 450°C for 60 minutes.

[0020] Secondly, the present invention provides an iron-based amorphous composite magnetic powder core prepared by the above-described preparation method.

[0021] As a preferred embodiment of the iron-based amorphous composite magnetic powder core of the present invention, under the test conditions of Bm=0.1T and 50kHz, the magnetic loss of the iron-based amorphous composite magnetic powder core is 240~355kW / cm. 3 Its permeability is 60~75.

[0022] As a preferred embodiment of the iron-based amorphous composite magnetic powder core of the present invention, under the test conditions of Bm=0.1T and 50kHz, the magnetic loss of the iron-based amorphous composite magnetic powder core is 240~295kW / cm. 3 Its permeability is 64~67 and its resistivity is 1.10~1.32Ω·m.

[0023] Thirdly, the present invention provides the application of the above-mentioned iron-based amorphous composite magnetic powder core in the preparation of power electronic devices.

[0024] The iron-based amorphous composite magnetic powder core of the present invention is suitable for high-frequency power electronic devices such as new energy vehicles, DC / DC converters, data center power modules, and photovoltaic inverters.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention uses Mn with intrinsic magnetic properties. 0.5 Zn 0.5 Fe2O4, as a coating agent, replaces traditional non-magnetic insulating materials to form a magnetic coating layer, creating an insulating structure between particles without producing a non-magnetic "magnetic dilution" effect. It can even maintain or improve the effective permeability of the magnetic powder core through magnetic coupling, resolving the fundamental contradiction in existing technologies where magnetic properties are sacrificed for insulation. Meanwhile, Mn... 0.5 Zn 0.5 Fe2O4 is a ferrite material with a resistivity much higher than that of metallic magnetic powder. As a coating layer, it can effectively cut off the electrical contact between magnetic particles, greatly improve the overall resistivity of the magnetic powder core, thereby significantly reducing high-frequency eddy current loss and improving soft magnetic properties at high frequencies.

[0026] The iron-based amorphous composite magnetic powder core of this invention exhibits a loss as low as 242.28 kW / m under test conditions of Bm=0.1T and 50kHz. 3 With a permeability between 60 and 75, it is suitable for high-frequency power electronic devices such as new energy vehicles, DC / DC converters, data center power modules, and photovoltaic inverters. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the preparation process of the iron-based amorphous composite magnetic powder core of the present invention; Figure 2 Mn of the present invention 0.5 Zn 0.5 Schematic diagram of the preparation process of Fe2O4; Figure 3 Mn prepared in Example 1 of this invention 0.5 Zn 0.5 TEM image of Fe2O4; Figure 4 Mn prepared in Example 1 of this invention 0.5 Zn 0.5 XRD pattern of Fe2O4; Figure 5 Mn prepared in Example 1 of this invention 0.5 Zn 0.5 VSM plot of Fe2O4; Figure 6 The images shown are SEM images of the microstructure of the coated magnetic powder obtained in step (1) of the preparation methods of Examples 1-4 and Comparative Examples 1 and 3 of the present invention. a represents Comparative Example 1, b represents Example 1, c represents Example 2, d represents Example 3, e represents Example 4, and f represents Comparative Example 3. Detailed Implementation

[0028] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0029] Unless otherwise specified, all other materials and reagents used in the examples are commercially available.

[0030] Example 1 An embodiment of the present invention provides a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, coat the surface of the amorphous FeSiB magnetic powder with a phosphoric acid passivation layer, and then add Mn 0.5 Zn 0.5 The hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder. Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 1:1:200; FeSiB is first coated with a phosphoric acid passivation layer, and then Mn is added. 0.5 Zn 0.5 Fe2O4 n-hexane dispersion, Mn 0.5 Zn 0.5 Fe2O4 is dispersed by n-hexane, and n-hexane is easy to volatilize during stirring, so it is more evenly coated on the magnetic powder when stirred with the magnetic powder. (2) The coated magnetic powder from step (1) is placed in an annealing furnace for the first annealing, held at 350℃ for 60 min, to remove stress and solidify the coating layer, thus obtaining annealed coated magnetic powder; the first annealing is a dual treatment of "stress relief + coating layer solidification" for the magnetic powder; phosphoric acid reacts with the surface of the magnetic powder to generate a phosphate passivation layer, and heating and annealing can make the passivation layer denser and more stable, and can also allow Mn 0.5 Zn 0.5 Fe2O4 particles are firmly anchored on the surface of FeSiB magnetic powder; (3) Mix the organosilicon resin (phenylmethyl silicone resin) with the annealed coated magnetic powder from step (2) and mix thoroughly by mechanical stirring; then add zinc stearate (lubricant) and mix thoroughly by mechanical stirring to obtain iron-based amorphous composite magnetic powder; The mass ratio of silicone resin to annealed coated magnetic powder is 1:200; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into a blank at a pressure of 1500 MPa. (5) The blank from step (4) is subjected to a second annealing at 450°C for 60 minutes to remove internal stress and obtain an iron-based amorphous composite magnetic powder core. The second annealing can remove the internal stress generated during the cold pressing process.

[0031] A schematic diagram of the preparation process of the iron-based amorphous composite magnetic powder core of the present invention is shown below. Figure 1 As shown, This embodiment utilizes Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is as follows: First, ferric chloride hexahydrate, sodium oleate, n-hexane, anhydrous ethanol, and deionized water are mixed and stirred, then degassed at 60℃. The organic phase is separated and n-hexane is evaporated to obtain the ferric-oleic acid complex. Then, the obtained ferric-oleic acid complex is mixed with oleic acid, 1-octadecene, and diphenyl ether, and heated to 200℃ under nitrogen protection. The temperature is then increased to 300℃ at a rate of 10℃ / min and held for 30 min. After the reaction is completed, the mixture is washed with ethanol, collected by centrifugation, dispersed in n-hexane, and the solvent is evaporated to obtain magnetic nanoparticles Mn. 0.5 Zn 0.5 Fe2O4.

[0032] This invention Mn 0.5 Zn 0.5 A schematic diagram of the Fe2O4 preparation process is shown below. Figure 2 As shown.

[0033] Mn prepared by transmission electron microscopy (TEM) was observed 0.5 Zn 0.5 Microstructure of Fe2O4.

[0034] Mn prepared in Example 1 0.5 Zn 0.5 TEM image of Fe2O4 as shown Figure 3 As shown. The results show that the prepared Mn 0.5 Zn 0.5 The average particle size of Fe2O4 is 15~50nm.

[0035] Mn prepared by X-ray diffraction (XRD, Ultima IV, Rigaku SmartLab SE) 0.5 Zn 0.5 XRD data for Fe2O4.

[0036] Mn prepared in Example 1 0.5 Zn 0.5 The XRD pattern of Fe2O4 is shown below. Figure 4 As shown. The results show that Mn 0.5 Zn 0.5 XRD pattern of Fe2O4 and spinel-type Mn 0.5 Zn 0.5 The diffraction peaks of Fe2O4 are consistent with the standard PDF card (PDF number #97-018-4159), corresponding to the (111), (220), (311), (400), (422), (440), and (511) crystal planes. No impurity peaks were detected, and a single-phase spinel structure was formed on the surface, successfully yielding Mn. 0.5 Zn 0.5 Fe2O4.

[0037] Mn prepared using VSM (Lakeshore 7410) observations 0.5 Zn 0.5 Magnetic properties of Fe2O4.

[0038] Mn prepared in Example 1 0.5 Zn 0.5 The VSM diagram of Fe2O4 is shown below. Figure 5 As shown. The results show that Mn 0.5 Zn 0.5 The saturation magnetization of Fe2O4 (M s The lowest coercivity (H) is 55 emu / g. c The value of 0.05 Oe (which is almost negligible) indicates that it exhibits superparamagnetic behavior at room temperature.

[0039] Compared to commercially available Mn 0.5 Zn 0.5 Fe2O4 nanoparticles (prepared by methods including coprecipitation, sol-gel, and hydrothermal methods), and Mn prepared by a specific method of this invention. 0.5 Zn 0.5 Fe2O4 has high M s (55 emu / g) and low H c (0.05 Oe, approximately 0), used for coating FeSiB to prepare magnetic powder cores, resulting in lower core loss. Meanwhile, commercially available Mn... 0.5 Zn 0.5 Fe2O4 nanoparticles typically exhibit significant morphological defects, are large (reaching the micrometer level), have a wide and irregular particle size distribution, and suffer from severe irreversible agglomeration. Using them to coat FeSiB can lead to increased loss in the prepared magnetic powder core.

[0040] Example 2 This invention provides an embodiment of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this embodiment and Embodiment 1 lies only in the Mn step (1). 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder is different. In this embodiment, Mn from Example 1 is used. 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder was adjusted from 1:200 to 1:100. Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0041] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then add Mn 0.5 Zn 0.5 A hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 2:1:200; (2) Place the coated magnetic powder from step (1) in an annealing furnace for the first annealing, hold at 350℃ for 60 min, and obtain annealed coated magnetic powder; (3) Mix the organosilicon resin (phenylmethyl silicone resin) with the annealed coated magnetic powder from step (2) and mix thoroughly by mechanical stirring; then add zinc stearate (lubricant) and mix thoroughly by mechanical stirring to obtain iron-based amorphous composite magnetic powder; The mass ratio of silicone resin to annealed coated magnetic powder is 1:200; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into a blank at a pressure of 1500 MPa. (5) The blank from step (4) is annealed for a second time and kept at 450°C for 60 minutes to obtain an iron-based amorphous composite magnetic powder core.

[0042] Example 3 This invention provides an embodiment of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this embodiment and Embodiment 1 lies only in the Mn step (1). 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder is different. In this embodiment, Mn from Example 1 is used. 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder was adjusted from 1:200 to 3:200. Mn 0.5 Zn0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0043] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then add Mn 0.5 Zn 0.5 A hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 3:1:200; (2) Place the coated magnetic powder from step (1) in an annealing furnace for the first annealing, hold at 350℃ for 60 min, and obtain annealed coated magnetic powder; (3) Mix the organosilicon resin (phenylmethyl silicone resin) with the annealed coated magnetic powder from step (2) and mix thoroughly by mechanical stirring; then add zinc stearate (lubricant) and mix thoroughly by mechanical stirring to obtain iron-based amorphous composite magnetic powder; The mass ratio of silicone resin to annealed coated magnetic powder is 1:200; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into a blank at a pressure of 1500 MPa. (5) The blank from step (4) is annealed for a second time and kept at 450°C for 60 minutes to obtain an iron-based amorphous composite magnetic powder core.

[0044] Example 4 This invention provides an embodiment of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this embodiment and Embodiment 1 lies only in the Mn step (1). 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder is different. In this embodiment, Mn from Example 1 is used. 0.5 Zn 0.5 The mass ratio of Fe₂O₄ to amorphous FeSiB magnetic powder was adjusted from 1:200 to 1:50. 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0045] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then add Mn 0.5 Zn 0.5 A hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder; Mn0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 4:1:200; (2) Place the coated magnetic powder from step (1) in an annealing furnace for the first annealing, hold at 350℃ for 60 min, and obtain annealed coated magnetic powder; (3) Mix the organosilicon resin (phenylmethyl silicone resin) with the annealed coated magnetic powder from step (2) and mix thoroughly by mechanical stirring; then add zinc stearate (lubricant) and mix thoroughly by mechanical stirring to obtain iron-based amorphous composite magnetic powder; The mass ratio of silicone resin to annealed coated magnetic powder is 1:200; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into a blank at a pressure of 1500 MPa. (5) The blank from step (4) is annealed for a second time and kept at 450°C for 60 minutes to obtain an iron-based amorphous composite magnetic powder core.

[0046] Example 5 This invention provides an embodiment of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this embodiment and Embodiment 2 lies only in the mass ratio of phosphoric acid to amorphous FeSiB magnetic powder in step (1). In this embodiment, the mass ratio of phosphoric acid to amorphous FeSiB magnetic powder in Embodiment 2 is adjusted from 1:200 to 1:100. Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0047] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then add Mn 0.5 Zn 0.5 A hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 1:1:100; (2) Place the coated magnetic powder from step (1) in an annealing furnace for the first annealing, hold at 350℃ for 60 min, and obtain annealed coated magnetic powder; (3) Mix the organosilicon resin (phenylmethyl silicone resin) with the annealed coated magnetic powder from step (2) and mix thoroughly by mechanical stirring; then add zinc stearate (lubricant) and mix thoroughly by mechanical stirring to obtain iron-based amorphous composite magnetic powder; The mass ratio of silicone resin to annealed coated magnetic powder is 1:200; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into a blank at a pressure of 1500 MPa. (5) The blank from step (4) is annealed for a second time and kept at 450°C for 60 minutes to obtain an iron-based amorphous composite magnetic powder core.

[0048] Example 6 This invention provides an embodiment of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this embodiment and Embodiment 1 lies only in the mass ratio of silicone resin to annealed coated magnetic powder in step (3). In this embodiment, the mass ratio of silicone resin to annealed coated magnetic powder in Embodiment 1 is adjusted from 1:200 to 1:100. Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0049] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then add Mn 0.5 Zn 0.5 A hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 1:1:200; (2) Place the coated magnetic powder from step (1) in an annealing furnace for the first annealing, hold at 350℃ for 60 min, and obtain annealed coated magnetic powder; (3) Mix the organosilicon resin (phenylmethyl silicone resin) with the annealed coated magnetic powder from step (2) and mix thoroughly by mechanical stirring; then add zinc stearate (lubricant) and mix thoroughly by mechanical stirring to obtain iron-based amorphous composite magnetic powder; The mass ratio of silicone resin to annealed coated magnetic powder is 1:100; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into a blank at a pressure of 1500 MPa. (5) The blank from step (4) is annealed for a second time and kept at 450°C for 60 minutes to obtain an iron-based amorphous composite magnetic powder core.

[0050] Example 7 This invention provides an embodiment of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The only difference between this embodiment and embodiment 2 is the temperature of the second annealing in step (5). In this embodiment, the temperature of the second annealing in embodiment 2, which was 450°C, is adjusted to 520°C. 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0051] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then add Mn 0.5 Zn 0.5 A hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 2:1:200; (2) Place the coated magnetic powder from step (1) in an annealing furnace for the first annealing, hold at 350℃ for 60 min, and obtain annealed coated magnetic powder; (3) Mix the organosilicon resin (phenylmethyl silicone resin) with the annealed coated magnetic powder from step (2) and mix thoroughly by mechanical stirring; then add zinc stearate (lubricant) and mix thoroughly by mechanical stirring to obtain iron-based amorphous composite magnetic powder; The mass ratio of silicone resin to annealed coated magnetic powder is 1:200; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into a blank at a pressure of 1500 MPa. (5) The blank from step (4) is annealed for a second time and kept at 520℃ for 60 minutes to obtain an iron-based amorphous composite magnetic powder core.

[0052] Comparative Example 1 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this comparative example and Example 2 is that Mn is not added in step (1). 0.5 Zn 0.5 Fe2O4 is only passivated and coated with phosphoric acid.

[0053] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this comparative example includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid and mechanically stir until fully mixed to obtain coated magnetic powder; the mass ratio of phosphoric acid to amorphous FeSiB magnetic powder is 1:200. (2) Same as Example 2; (3) Same as Example 2; (4) Same as Example 2; (5) Same as Example 2.

[0054] Comparative Example 2 This invention provides a comparative example of a dual-magnetic phase iron-based amorphous composite magnetic powder core. The difference between this comparative example and Example 2 is that in step (1), non-magnetic nano-SiO2 is used to replace Mn. 0.5 Zn 0.5 Fe2O4.

[0055] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this comparative example includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then grow a SiO2 layer on the surface of FeSiB magnetic powder using the sol-gel method to prepare FeSiB / SiO2 magnetic powder with core-shell structure, i.e. coated magnetic powder. (2) Same as Example 2; (3) Same as Example 2; (4) Same as Example 2; (5) Same as Example 2.

[0056] Comparative Example 3 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this comparative example and Example 1 lies only in the Mn step (1). 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder is different. In this comparative example, Mn from Example 1 is used. 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder was adjusted from 1:200 to 5:200. Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0057] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then add Mn 0.5 Zn 0.5 A hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 5:1:200; (2) Same as Example 1; (3) Same as Example 1; (4) Same as Example 1; (5) Same as Example 1.

[0058] Comparative Example 4 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this comparative example and Example 2 lies only in the Mn step (1). 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder is different. In this comparative example, Mn from Example 2 is used. 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder was adjusted from 1:100 to 1:20. 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0059] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this comparative example includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, and then add Mn 0.5 Zn 0.5 A hexane dispersion of Fe2O4 was thoroughly mixed by mechanical stirring to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to phosphoric acid and amorphous FeSiB magnetic powder is 10:1:200; (2) Same as Example 2; (3) Same as Example 2; (4) Same as Example 2; (5) Same as Example 2.

[0060] Comparative Example 5 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this comparative example and Example 2 is that in step (3), no silicone resin is added; only a lubricant is added. Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0061] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this comparative example includes the following steps: (1) Same as Example 2; (2) Same as Example 2; (3) Mix zinc stearate (lubricant) with the annealed coated magnetic powder from step (2) and mechanically stir to mix thoroughly and evenly; to obtain iron-based amorphous composite magnetic powder; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into a blank at a pressure of 1500 MPa. (5) The blank from step (4) is annealed for the second time, and kept at 450℃ for 60 minutes to remove internal stress and obtain iron-based amorphous composite magnetic powder core.

[0062] Comparative Example 6 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The only difference between this comparative example and Example 2 is the absence of the first annealing. Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0063] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this comparative example includes the following steps: (1) Same as Example 2; (2) Mix the organosilicon resin (phenylmethyl silicone resin) with the coated magnetic powder from step (1) and stir mechanically until fully mixed; then add zinc stearate (lubricant) and stir mechanically until fully mixed to obtain iron-based amorphous composite magnetic powder; The mass ratio of silicone resin to annealed coated magnetic powder is 1:200; The mass ratio of zinc stearate to annealed coated magnetic powder is 1:200; (3) The iron-based amorphous composite magnetic powder from step (2) is cold-pressed into a blank at a pressure of 1500 MPa. (4) The blank from step (3) is annealed for a second time and kept at 450°C for 60 minutes to obtain an iron-based amorphous composite magnetic powder core.

[0064] Comparative Example 7 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The only difference between this comparative example and Example 2 is the absence of a second annealing process. Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is the same as in Example 1.

[0065] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this comparative example includes the following steps: (1) Same as Example 2; (2) Same as Example 2; (3) Same as Example 2; (4) The iron-based amorphous composite magnetic powder from step (3) is cold-pressed into shape with a pressing pressure of 1500 MPa to obtain an iron-based amorphous composite magnetic powder core.

[0066] Comparative Example 8 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this comparative example and Example 2 lies only in the Mn step (1). 0.5 Zn 0.5The coating method of Fe2O4 is different, refer to CN110428967A.

[0067] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this comparative example includes the following steps: (1) Amorphous FeSiB magnetic powder was dispersed in a solution of manganese chloride, zinc chloride, and ferric chloride (the molar ratio of Mn, Zn, and Fe elements was 0.5:0.5:2). After stirring evenly, the pH of the mixture was adjusted to 10.5 using ammonia water, and stirring was continued for 0.5 h. Then, the mixture was allowed to stand in an 80℃ water bath for 4 h to form a sol state. The resulting sol product was then dried for 4 h to a gel state. Finally, it was pretreated at 500℃ for 1 h to generate ferrite (FeSiB@Mn) from the ferrite precursor. 0.5 Zn 0.5 Fe2O4), then FeSiB@Mn 0.5 Zn 0.5 Fe2O4 and phosphoric acid are mixed evenly to obtain coated magnetic powder; (2) Same as Example 2; (3) Same as Example 2; (4) Same as Example 2; (5) Same as Example 2.

[0068] Comparative Example 9 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The difference between this comparative example and Example 2 lies only in the Mn step (1). 0.5 Zn 0.5 The Fe2O4 particles have different sizes. In this comparative example, Mn from Example 2 has an average particle size of approximately 15-50 nm. 0.5 Zn 0.5 The Fe2O4 particles were adjusted to have an average particle size of approximately 55-70 nm.

[0069] Referring to Mn in Example 1 0.5 Zn 0.5 The method for preparing Fe2O4 yielded Mn with an average particle size of approximately 55–70 nm. 0.5 Zn 0.5 Fe2O4.

[0070] Comparative Example 10 This invention provides a comparative example of a dual-magnetic-phase iron-based amorphous composite magnetic powder core. The only difference between this comparative example and Example 2 is the ferrite used in step (1). This comparative example uses the ferrite Mn from Example 2. 0.5 Zn 0.5 Fe2O4 was adjusted to Fe3O4 nanoparticles with an average particle size of 15 nm.

[0071] Specifically, the preparation method of the iron-based amorphous composite magnetic powder core in this embodiment includes the following steps: (1) Mix amorphous FeSiB magnetic powder with phosphoric acid, then add hexane dispersion of Fe3O4, and mechanically stir to mix thoroughly to obtain coated magnetic powder; the mass ratio of Fe3O4 to phosphoric acid and amorphous FeSiB magnetic powder is 2:1:200. (2) Same as Example 2; (3) Same as Example 2; (4) Same as Example 2; (5) Same as Example 2.

[0072] Test Example 1 The microstructure of the coated magnetic powder obtained in step (1) of the preparation method of the examples and comparative examples was observed using a scanning electron microscope (SEM).

[0073] SEM images of the microstructure of the coated magnetic powder obtained by step (1) of the preparation method in Examples 1-4 and Comparative Examples 1 and 3 are shown below. Figure 6 As shown, a represents Comparative Example 1, b represents Example 1, c represents Example 2, d represents Example 3, e represents Example 4, and f represents Comparative Example 3. The results show that the FeSiB powder surface is smooth and flat (Comparative Example 1), with no obvious impurities. When Mn... 0.5 Zn 0.5 When the Fe2O4 content increased from 0.0% (Comparative Example 1) to 1.0% (Example 2), the nanoparticles were uniformly deposited on the powder surface to form an adhered insulating layer; however, when the content was further increased to 1.5-2.5% (Examples 3-4, Comparative Example 3), the nanoparticles were excessively aggregated and formed island-like agglomerates on the surface.

[0074] Test Example 2 The permeability and magnetic loss of the iron-based amorphous composite magnetic powder cores in the examples and comparative examples were measured using a BH analyzer (IWATSU, SY-8219) under the following conditions: Bm = 100 mT, f = 50 kHz.

[0075] The resistivity of the iron-based amorphous composite magnetic powder cores of the examples and comparative examples was tested using a digital four-point probe resistivity meter (ST2253y) at room temperature, with an error of ±0.1% and a reading of ±2.

[0076] The results of permeability, magnetic loss, and resistivity of the iron-based amorphous composite magnetic powder cores of Examples 1-7 and Comparative Examples 1-10 are shown in Table 1. Table 1 Table 1 shows that the magnetic loss of the iron-based amorphous composite magnetic powder core prepared in this invention is approximately 240~355 kW / cm. 3 Its magnetic permeability is approximately 60-75.

[0077] Compared to Example 2, Comparative Example 1 lacks Mn. 0.5 Zn 0.5 Fe2O4 ferrite coating significantly improved the magnetic loss and significantly reduced the permeability of the prepared composite magnetic powder core, indicating that Mn 0.5 Zn 0.5 Fe2O4 ferrite coating is essential.

[0078] Compared to Example 2, Comparative Example 2 uses nano-SiO2 to replace Mn. 0.5 Zn 0.5 The composite magnetic powder core prepared with Fe2O4 showed significantly improved magnetic loss and significantly reduced magnetic permeability, indicating that Mn 0.5 Zn 0.5 Fe2O4 ferrite coating represents a significant improvement over SiO2.

[0079] Compared with Example 2, Comparative Examples 3 and 4 utilize Mn coating. 0.5 Zn 0.5 The high Fe2O4 ferrite content significantly increases the magnetic loss of the prepared composite magnetic powder core, indicating that Mn... 0.5 Zn 0.5 Fe2O4 ferrite needs to meet specific addition amounts.

[0080] Compared with Example 2, Comparative Examples 6 and 7 lacked either the first annealing or the second annealing during preparation. The magnetic loss of the prepared composite magnetic powder core was significantly increased and the magnetic permeability was significantly reduced, indicating that the first annealing and the second annealing must be satisfied simultaneously.

[0081] Compared to Example 2, the ferrite particles coated according to CN110428967A in Comparative Example 8 were prepared using a sol-gel method. These ferrite particles had a larger particle size and poorer dispersibility, resulting in significantly greater coercivity than the Mn particles prepared in Example 1 of this invention. 0.5 Zn 0.5 Fe2O4 leads to increased loss in the prepared magnetic powder core.

[0082] Compared with Example 2, Comparative Example 9 uses Mn 0.5 Zn 0.5 The increased particle size of Fe2O4 ferrite significantly improves the magnetic loss of the prepared composite magnetic powder core.

[0083] Compared to Example 2, Comparative Example 10 uses Mn 0.5 Zn 0.5 Replacing Fe2O4 ferrite with Fe3O4 ferrite significantly improves the magnetic loss of the prepared composite magnetic powder core.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a dual-magnetic-phase iron-based amorphous composite magnetic powder core, characterized in that, Includes the following steps: S1. Mix amorphous FeSiB magnetic powder with phosphoric acid, then add Mn 0.5 Zn 0.5 Fe2O4 organic solvent dispersion was thoroughly mixed to obtain coated magnetic powder; Mn 0.5 Zn 0.5 The mass ratio of Fe2O4 to amorphous FeSiB magnetic powder is 1~4:200; Mn 0.5 Zn 0.5 The average particle size of Fe2O4 is 15~50nm; S2. The coated magnetic powder from step S1 is subjected to a first annealing to remove stress and solidify the coating layer, resulting in annealed coated magnetic powder. S3. Mix the silicone resin with the annealed coated magnetic powder from step S2 until fully mixed; then add the lubricant and mix thoroughly to obtain iron-based amorphous composite magnetic powder. S4. The iron-based amorphous composite magnetic powder from step S3 is cold-pressed to form a blank; S5. The blank from step S4 is subjected to a second annealing to remove internal stress and obtain an iron-based amorphous composite magnetic powder core.

2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of phosphoric acid to amorphous FeSiB magnetic powder is 1~2:200; And / or, in step S1, the organic solvent includes n-hexane, acetone, or ethanol.

3. The preparation method according to claim 1, characterized in that, In step S1, the Mn 0.5 Zn 0.5 The preparation method of Fe2O4 is as follows: Ferric chloride hexahydrate, sodium oleate, n-hexane, anhydrous ethanol, and deionized water are mixed, degassed, the organic phase is separated, and n-hexane is evaporated to obtain an iron-oleic acid complex. The obtained iron-oleic acid complex is mixed with oleic acid, 1-octadecene, and diphenyl ether, and heated to 200℃ under nitrogen protection. The temperature is then increased to 300℃ at a rate of 10℃ / min and held for 30 min. After the reaction is complete, the mixture is washed with ethanol, collected by centrifugation, dispersed in n-hexane, and the solvent is evaporated to obtain magnetic nanoparticles Mn. 0.5 Zn 0.5 Fe2O4.

4. The preparation method according to claim 1, characterized in that, In step S2, the conditions for the first annealing are 300~400℃ for 30~90 minutes; And / or, in step S3, the mass ratio of the silicone resin to the annealed coated magnetic powder is 1:100~200; And / or, in step S3, the mass ratio of the lubricant to the annealed coated magnetic powder is 1:100~1000.

5. The preparation method according to claim 1, characterized in that, In step S3, the silicone resin includes methyl silicone resin or phenylmethyl silicone resin; the lubricant includes zinc stearate or magnesium stearate.

6. The preparation method according to claim 1, characterized in that, In step S4, the pressure of the cold pressing is 1000~3000 MPa.

7. The preparation method according to claim 1, characterized in that, In step S5, the conditions for the second annealing are 400~600℃ for 10~180 min.

8. An iron-based amorphous composite magnetic powder core prepared by the preparation method according to any one of claims 1 to 7.

9. The iron-based amorphous composite magnetic powder core as described in claim 8, characterized in that, Under test conditions of Bm=0.1T and 50kHz, the magnetic loss of the iron-based amorphous composite magnetic powder core is 240~355kW / cm. 3 Its magnetic permeability is 60~75.

10. The application of the iron-based amorphous composite magnetic powder core according to claim 8 in the preparation of power electronic devices.

Citation Information

Patent Citations

  • Preparation method of ultralow-temperature cold-sintered iron-based nanocrystalline composite magnetic powder core and product

    CN110428967A